2013
DOI: 10.1016/j.cell.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

OTULIN Antagonizes LUBAC Signaling by Specifically Hydrolyzing Met1-Linked Polyubiquitin

Abstract: SummaryThe linear ubiquitin (Ub) chain assembly complex (LUBAC) is an E3 ligase that specifically assembles Met1-linked (also known as linear) Ub chains that regulate nuclear factor κB (NF-κB) signaling. Deubiquitinases (DUBs) are key regulators of Ub signaling, but a dedicated DUB for Met1 linkages has not been identified. Here, we reveal a previously unannotated human DUB, OTULIN (also known as FAM105B), which is exquisitely specific for Met1 linkages. Crystal structures of the OTULIN catalytic domain in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
674
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 428 publications
(695 citation statements)
references
References 56 publications
21
674
0
Order By: Relevance
“…S4 B and C). OTULIN cleaves Met1-linked linear polyubiquitin chains from target substrates, such as NEMO (IKKγ), RIPK1, ASC, and TNFR1 to restrict signaling activation and propagation (7,14,15). To investigate the effect of OTULIN mutations on its deubiquitinase function, we cotransfected WT and mutant OTULIN plasmids into HEK293 cells along with plasmids encoding the LUBAC subunits, mono specific-ubiquitin plasmid, and each of the OTULIN substrates NEMO (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…S4 B and C). OTULIN cleaves Met1-linked linear polyubiquitin chains from target substrates, such as NEMO (IKKγ), RIPK1, ASC, and TNFR1 to restrict signaling activation and propagation (7,14,15). To investigate the effect of OTULIN mutations on its deubiquitinase function, we cotransfected WT and mutant OTULIN plasmids into HEK293 cells along with plasmids encoding the LUBAC subunits, mono specific-ubiquitin plasmid, and each of the OTULIN substrates NEMO (Fig.…”
Section: Significancementioning
confidence: 99%
“…OTULIN and CYLD are deubiquitinases (DUBs) that cleave Met1-linked chains (6). Although OTULIN functions exclusively as a Met1 deubiquitinase (7,8), CYLD may also hydrolyze Lys63-linked ubiquitin (9). OTULIN is an evolutionarily highly conserved protein, and in mice complete deficiency is embryonically lethal (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%